2014
DOI: 10.1016/j.cmet.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

γ-Butyrobetaine Is a Proatherogenic Intermediate in Gut Microbial Metabolism of L-Carnitine to TMAO

Abstract: Summary L- Carnitine, a nutrient in red meat, was recently reported to accelerate atherosclerosis via a metaorganismal pathway involving gut microbial trimethylamine (TMA) formation and host hepatic conversion into trimethylamine-N-oxide (TMAO). Herein we show that following L-carnitine ingestion, γ-butyrobetaine (γBB) is produced as an intermediary metabolite by gut microbes at a site anatomically proximal to and at a rate ~1000-fold higher than the formation of TMA. Moreover, we show γBB is the major gut mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
460
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 465 publications
(493 citation statements)
references
References 40 publications
12
460
2
8
Order By: Relevance
“…TMAO is derived primarily from dietary choline and carnitine through the action of gut microbiota, which metabolize these constituents to trimethylamine (TMA) 1, 11, 12. TMA is absorbed in turn and travels via the portal circulation to the liver, where it is oxidized by flavin‐containing monoxygenases, primarily FMO3, to TMAO 1, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMAO is derived primarily from dietary choline and carnitine through the action of gut microbiota, which metabolize these constituents to trimethylamine (TMA) 1, 11, 12. TMA is absorbed in turn and travels via the portal circulation to the liver, where it is oxidized by flavin‐containing monoxygenases, primarily FMO3, to TMAO 1, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…TMA is absorbed in turn and travels via the portal circulation to the liver, where it is oxidized by flavin‐containing monoxygenases, primarily FMO3, to TMAO 1, 11, 12. In studies in mice, supplementation with dietary choline, carnitine, precarnitine (γ‐butyrobetaine) , or even TMAO alone was sufficient to enhance macrophage cholesterol accumulation and atherogenic plaque formation, supporting a causal relationship 1, 2, 11. TMAO also has significant effects on cholesterol metabolism in the bile acid compartments 1, 11…”
Section: Introductionmentioning
confidence: 99%
“…3 Based on the relationship between GabaBet, carnitine, and TMAO, it has been hypothesized that intestinal microbiota may contribute to the wellestablished link between high levels of Lcarnitine consumption and CVD risk and that GabaBet could be related to the presence of carotid atherosclerosis and its complications linked to high levels of TMAO. 3 A study conducted on a cohort of 264 patients with carotid atherosclerosis reported increased serum levels of GabaBet and TML, but not TMAO. 23 However, a direct role of GabaBet in atherogenesis has been questioned.…”
Section: Discussionmentioning
confidence: 99%
“…A deeper characterization of the metabolism and the molecular mechanism(s) of action of this betaine is critical to understand the differences with GabaBet intermediate in gut microbial metabolism of Lcarnitine to TMAO. 3 Furthermore, future investigations might be helpful in the elucidation of the possible effect of GabaBet on SIRT6 modulation. 10 Indeed, both SIRT1 and SIRT6, showing an established role in the protection against CVD and hGluc-induced endothelial senescence, 30 could be crucial targets in the setting of natural bioactive compounds able to limit the cellular oxidative processes responsible for the onset of diabetes and its vascular complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation